KONSEPSI MASYARAKAT MADANI DALAM BINGKAI PENDIDIKAN ISLAM - Mughniatul Ilma; Rifqi Nur Alfian (IAIN Ponorogo, 2020)
The challenge of globalization is increasingly rocking the social order in society. This can be a real threat to a nation if it is continuously allowed to flow without any meaningful effort. Various problems arise including moral decadence, moral degradation to the disintegration of the nation. This requires a revolution in the social system of society. Civil society as an old concept which became known as 'Islamic' with the term Civil Society became important to be made a proposal for change. Civil society is the ideal form of society that all nations aspire to. The building of civil society requires a variety of solid and resilient materials based on the foundation of religion. The key to the building is Islamic Education. Islamic education is an effort to create a superior generation that is Islamic, which in turn will unite itself to form a religious, moral, high quality and creative society in building civilization.